THE EFFECT OF FINANCING TO DEPOSIT RATIO, CAPITAL ADEQUENCY RATIO, NON-PERFORMING FINANCING ON NET PROFIT MARGIN (CASE STUDY OF BANK MUAMMALAT SYARIAH 2018-2022) - Muhammad Distian Andi Hermawan (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2023)
The purpose of this study is to determine the simultaneous or partial effect of FDR, CAR and MFN variables on net profit. The data source used in this study is secondary data. The results showed that the significance value of the variable Financing Ratio / FDR (X1) Capital Mobilization Ratio / FDR did not have a significant effect on the variables Net Income Ratio (Y), solvency and capital. variable modal fitness. Ratio / CAR then it can be said that the solvency ratio variable does not have a significant effect on profit margin (Y). Simultaneous significance level test results. In this case it can be said.